Sierra Leone: Education Country Status Report: An analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2013)
KerkoCite.ItemAlsoKnownAs: 2405685:FWX5GT4H

The Agenda for Prosperity: Road to Middle Income Status - Government of Sierra Leone (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:FHMH4G7H 2405685:7DIVY6PP
Keywords: ⛔ No DOI found

Republic of Sierra Leone Higher and Tertiary Education Sector Policy Note - World Bank (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:ANFH2ALH 2405685:QAFBTUE9

10 principles to consider when introducing ICTs into remote, low-income educational environments - Trucano, Michael (World Bank Blogs, 2013)
there must be an I, a C, and a T here somewhere ... There are, broadly speaking, two strands of concurrent thinking that dominate discussions around the use of new technologies in education around the world. At one end of the continuum, talk is dominated by words like 'transformation'. The ...
Library Catalog: blogs.worldbank.org KerkoCite.ItemAlsoKnownAs: 2339240:5I5XNP44 2339240:7ENMXVAZ 2339240:7TDXW2WT 2339240:M7NFMPY5 2405685:23SM2GHY 2405685:2KLF59UJ 2405685:4QHLLY7H 2405685:BJSJWEMM 2405685:EJG6JBSL 2405685:EY7WAUHY 2405685:MDR3XLXP 2405685:N584ISNZ 2405685:RCHYAVL3 2405685:SVDWLWHS 2405685:XED3H9S7 4042040:MXSNKXZ5 4656463:P4BDEDD3 4656463:YXDWWIE2